Adverse childhood experiences, resilience, and cannabis use in early motherhood - Roland, Alysa; Charron, Elizabeth; Shreffler, Karina M. (Frontiers in Psychiatry, 2025)
BackgroundExposure to Adverse Childhood Experiences (ACEs) is associated with increased risk of substance use in women, including cannabis use during pregnancy. Less is known, however, about how resilience factors moderate the association of ACEs on cannabis use in early motherhood.MethodsWe used survey data from 126 predominately low-income and diverse mothers enrolled in a longitudinal study in the South Central U.S. Multiple logistic regression models evaluated associations between ACEs and cannabis use through three years postpartum, stratified by resilience scores (median split). Adjusted models controlled for sociodemographic factors, postnatal depression, and prenatal substance use. Average predicted probabilities were estimated from fully adjusted models.ResultsAmong individuals with high resilience, each unit increase in ACEs was associated with significantly higher odds of cannabis use in early motherhood (adjusted OR = 1.38; 95% CI: 1.07–1.78). No significant association was observed among those with low resilience (adjusted OR = 1.02; 95% CI: 0.77–1.34). In the high resilience group, the average predicted probability of cannabis use increased from 8.5% at 0 ACEs to 62.9% at 10 ACEs; in the low resilience group, average predicted probabilities of cannabis use was high (~36%) regardless of ACE score.ConclusionsThe findings suggest that although ACEs are a social determinant of cannabis use in early motherhood, resilience may be protective, particularly among those with low and moderate ACE exposure. However, its protective effect diminishes with higher ACE exposure.